Effect of Flow Rate Ratio of Air and Waste Cooking Oil on Combustion Temperature and Furnace Efficiency - Idris, M.; Setyawan, Martomo; Suharto, Totok Eka (Eksergi, 2025)
Using waste cooking oil as an alternative fuel can reduce dependence on fossil fuels and address the problem of waste oil. This study aims to analyze the effect of the flow rate ratio of air and waste cooking oil on combustion characteristics and efficiency of domestic furnace. The experiment started with fuel characterization, including density, viscosity, flash point, and calorific value tests. The combustion process was carried out by varying the fuel and airflow to the furnace. Experiments included flame temperature measurements, water boiling tests, and measurements of heat uptake efficiency by the pot water. The results showed that the highest combustion temperature of 925.55℃ was achieved at an airflow rate of 21.3 m/s with a fuel flow rate of 1.05 L/hour. The flue gas emission temperature and furnace efficiency increased as the airflow rate and fuel discharge increased. The ratio also produces the fastest water boiling time of 2 minutes with the efficiency of heat uptake by water in the pot of 34.12%. The highest heat uptake efficiency by the water in the pot was obtained at the ratio of used cooking oil discharge of 0.6 L/hour with an airflow rate of 12.1 m/s at 43.12%. These results demonstrate the potential of waste cooking oil as an alternative fuel for efficient domestic combustion devices, with proper air supply to achieve optimal combustion.